(untitled) (European Journal of Pure and Applied Mathematics, 2020)
This work is devoted to evaluate the performances of the MOMA-plus method inÂ solving multiobjective optimization problems. This assessment is doing on the complexity of itsÂ algorithm, the convergence and the diversity of solutions in relation to the Pareto front. All theseÂ parameters were evaluated on non-linear multiobjective test problems and obtained solutions areÂ compared with those provided by the NSGA-II method. This comparative study made it possible to highlight the performances of MOMA-plus method for solving non-linear multiobjective problems.